2005
DOI: 10.1128/iai.73.10.6962-6973.2005
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Matrix Metalloproteinases Subsequent to UrogenitalChlamydia muridarumInfection of Mice

Abstract: The central hypothesis of this study was that matrix metalloproteinases (MMPs) would be enhanced following murine chlamydial infection and that their expression would vary in mouse strains that differ in their susceptibility to chronic chlamydia-induced disease. To address this hypothesis, female C3H/HeN and C57BL/6 mice were infected intravaginally with Chlamydia muridarum. Uterine and oviduct tissues were assessed for transcription of MMP genes and their tissue inhibitors. An increased activity of MMP genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
64
2
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(73 citation statements)
references
References 50 publications
6
64
2
1
Order By: Relevance
“…rCPAFϩIL-12-vaccinated animals also had lower frequen- (4,25,41). Therefore, reduction of PMN infiltration into the oviductal and mesosalpingeal tissues at an earlier point during the course of chlamydial infection also might account for the observed protection against upper genital tract pathology in vaccinated mice.…”
Section: Discussionmentioning
confidence: 93%
“…rCPAFϩIL-12-vaccinated animals also had lower frequen- (4,25,41). Therefore, reduction of PMN infiltration into the oviductal and mesosalpingeal tissues at an earlier point during the course of chlamydial infection also might account for the observed protection against upper genital tract pathology in vaccinated mice.…”
Section: Discussionmentioning
confidence: 93%
“…34 TNF is highly expressed during episodes of conjunctival inflammation in these subjects with trichiasis (M Burton, personal communication) and may influence risk of disease progression in relation to the spectrum of TNF-inducible genes, such as matrix metalloprotease 9 that may be important in initiating fibrosis. 35,36 We studied SNPs capturing common genetic variation within 25 kb of genome within the MHC region. The study suggests that host genetic variation at the TNF locus may affect risk of severe trachoma, but also that variation affecting related neighboring genes such as LTA, whose role in infectious, autoimmune and other disorders has started to be defined 13,[37][38][39] may be important.…”
Section: Discussionmentioning
confidence: 99%
“…However, elevated levels of IL-17 have been associated with increased disease susceptibility during C. muridarum respiratory tract infection via recruitment of neutrophils (16,47). Enhanced neutrophil influx and neutrophil release of matrix metalloproteases has been directly linked to tissue pathology in mouse models of C. muridarum genital tract infection (34,37). In addition, human studies have suggested that increased neutrophil activation has been associated with increased genital tract disease in females infected with C. trachomatis (43).…”
Section: Interleukin 17 (Il-17) Contributes To Development Of Th1 Immmentioning
confidence: 99%